Justice as an aspect of the polis idea in solon's political poems : a reading of the fragments in light of the of the researches of new classical archaeology. - Almeida, Joseph A. (Mnemosyne, Supplements, 2003)
This book examines the meaning of justice or dike in the political poems of Solon from a new interpretative perspective. The first two chapters argue that neither standard historical nor literary treatments have provided an adequate foundation for understanding Solon's dike . The main defect lies in an inability to connect Solon's concrete political work with his poetic perceptions. The book's central proposal is that the polis idea, from new classical archaeology, provides an objective standard for an interpretation of Solon's dike , which remedies this defect. The third chapter sets forth the polis idea, which becomes the measure for an examination, in the final two chapters, of Solon's view of dike . The book thus exhibits an interdisciplinary approach to Archaic poetry.